THU0073 HAVE THE CLINICAL CHARACTERISTICS OF RHEUMATOID ARTHRITIS AT PRESENTATION BECOME MILDER OVER TIME? RESULTS FROM A NATIONWIDE STUDY OVER THREE DECADES IN SWEDEN. (June 2019) - Einarsson, Jon; Olofsson, Tor; Palsson, Olafur; Wallman, Johan K; Kapetanovic, Meliha C
Abstract : Background: The course of rheumatoid arthritis (RA) has become milder during the last decades, which could at least partly be attributed to major advances in the pharmacological treatment of the disease and the implementation of "treat to target"-strategies (1, 2). It has also been suggested that RA is already milder at presentation (3) Objectives: To investigate whether the clinical status, markers of inflammation, functional status, and patient and evaluator reported disease activity measures in patients with newly diagnosed RA, have improved over the recent decades. Methods: Baseline data on all DMARD-naïve patients with early RA (<6 months duration) included in the nationwide Swedish Rheumatology Quality registry (SRQ) between 1991 and 2014 were retrieved. The RA diagnosis relied on the clinical judgement of the treating physician and the information comprised swollen and tender joints count (SJC; TJC), markers of inflammation (CRP; ESR), functional status (HAQ; 0-3), patient's and evaluator's assessment of global disease activity (PtGA; EGA) and patient's assessment of pain (on a visual analog scale, VAS; 0-100 mm). Baseline demographic and disease characteristics were compared between patients with disease onset 1991-2000 vs. those with onset 2011-2014, using Mann-Whitney U test and Pearson's chi-squared test. Results: A total of 6559 early RA patients were included. Over the study period of 23 years the majority of the patients were women (68%), and the mean age at inclusion increased from 57, 4 to 59, 1 years. Results are summarised in Table 1 . Mean CRP, ESR, TJC and SJC all decreased significantly between the two time periods compared, which was also the case for HAQ. In contrast, mean pain, PtGA and EGA increased significantly between the time periods. Furthermore, time from symptom onset to inclusion was shorter 2011-2014. Conclusion: In Swedish patients with early RA, baseline joint counts and inflammatory markers improved over the last three decades. This could partly be explained by shorter symptom duration at diagnosis but also suggests that, at onset, RA might be an inherently milder disease today. However, pain and patient's global assessment and evaluator's global assessment of disease activity increased over the same period of time, possibly indicating changes in both patients' and evaluators' expectations for management of early RA today References: [1] Gwinnutt, et al. Arthritis Rheumatol. 2017; 69:1566–75. [2] Matsumoto, et al. J Rheumatol. 2017; 44:1575–82. [3] Diffin, et al. J Rheumatol. 2014; 41:1590–9. Disclosure of Interests: Jon Einarsson: None declared, Tor Olofsson: None declared, Olafur Palsson: None declared, Johan K Wallman Consultant for: Consultant for AbbVie, Celgene, Eli Lilly, Novartis, and UCB Pharma., Meliha C Kapetanovic: None declared